Growth duration is a better predictor of stem increment than carbon supply in a Mediterranean oak forest: implications for assessing forest productivity under climate change - Lempereur, Morine; Martin‐StPaul, Nicolas K.; Damesin, Claire; Joffre, Richard; Ourcival, Jean‐Marc; Rocheteau, Alain; Rambal, Serge (The New phytologist, 2015)
Understanding whether tree growth is limited by carbon gain (source limitation) or by the direct effect of environmental factors such as water deficit or temperature (sink limitation) is crucial for improving projections of the effects of climate change on forest productivity. We studied the relationships between tree basal area (BA) variations, eddy covariance carbon fluxes, predawn water potential (Ψpd) and temperature at different timescales using an 8-yr dataset and a rainfall exclusion experiment in a Quercus ilex Mediterranean coppice. At the daily timescale, during periods of low temperature (< 5°C) and high water deficit (< −1.1 MPa), gross primary productivity and net ecosystem productivity remained positive whereas the stem increment was nil. Thus, stem increment appeared limited by drought and temperature rather than by carbon input. Annual growth was accurately predicted by the duration of BA increment during spring (Δt t0–t1). The onset of growth (t 0) was related to winter temperatures and the summer interruption of growth (t 1) to a threshold Ψpd value of −1.1 MPa. We suggest that using environmental drivers (i.e. drought and temperature) to predict stem growth phenology can contribute to an improvement in vegetation models and may change the current projections of Mediterranean forest productivity under climate change scenarios.